Parabolic Flow on Metric Measure Spaces - Prado-Castillo, H (2014)
We present parabolic equations on metric measure spaces. We prove existence and uniqueness of solutions. Under some assumptions the existence of global in time solution is proved. Moreover, regularity and qualitative property of the solutions are shown. © 2013 The Author(s).